Cost accounting : a managerial emphasis - Datar, Srikant M.; Foster, George; Rajan, Madhav; Ittner, Christopher (Upper Saddle River, NJ : Prentice Hall Inc, 2009)
This manual contains the fully worked-out and accuracy-checked solutions for selected end-of-chapter problems in the text.
Includes index.
To accompany: Cost accounting : a managerial emphasis / Charles T. Horngren [and others]. 13th ed.
Keywords: Managerial accounting. -- Textbooks